The histone demethylase Jumonji domain-containing protein 3 (JMJD3) regulates fibroblast activation in systemic sclerosis - Bergmann, Christina; Brandt, Adrian; Merlevede, Benita; Hallenberger, Ludwig; Dees, Clara; Wohlfahrt, Thomas; Pötter, Sebastian; Zhang, Yun; Chen, Chih-Wei; Mallano, Tatjana; Liang, Ruifang; Kagwiria, Rosebeth; et al. (Annals of the Rheumatic Diseases, 2017)
Systemic sclerosis (SSc) fibroblasts remain activated even in the absence of exogenous stimuli. Epigenetic alterations are thought to play a role for this endogenous activation. Trimethylation of histone H3 on lysine 27 (H3K27me3) is regulated by Jumonji domain-containing protein 3 (JMJD3) and ubiquitously transcribed tetratricopeptide repeat on chromosome X (UTX) in a therapeutically targetable manner. The aim of this study was to explore H3K27me3 demethylases as potential targets for the treatment of fibrosis.JMJD3 was inactivated by small interfering RNA-mediated knockdown and by pharmacological inhibition with GSKJ4. The effects of targeted inactivation of JMJD3 were analysed in cultured fibroblasts and in the murine models of bleomycin-induced and topoisomerase-I (topoI)-induced fibrosis. H3K27me3 at the FRA2 promoter was analysed by ChIP.The expression of JMJD3, but not of UTX, was increased in fibroblasts in SSc skin and in experimental fibrosis in a transforming growth factor beta (TGF?)-dependent manner. Inactivation of JMJD3 reversed the activated fibroblast phenotype in SSc fibroblasts and prevented the activation of healthy dermal fibroblasts by TGF?. Pharmacological inhibition of JMJD3 ameliorated bleomycin-induced and topoI-induced fibrosis in well-tolerated doses. JMJD3 regulated fibroblast activation in a FRA2-dependent manner: Inactivation of JMJD3 reduced the expression of FRA2 by inducing accumulation of H3K27me3 at the FRA2 promoter. Moreover, the antifibrotic effects of JMJD3 inhibition were reduced on knockdown of FRA2.We present first evidence for a deregulation of JMJD3 in SSc. JMJD3 modulates fibroblast activation by regulating the levels of H3K27me3 at the promoter of FRA2. Targeted inhibition of JMJD3 limits the aberrant activation of SSc fibroblasts and exerts antifibrotic effects in two murine models.
EVALuna2:13457